Measuring the end-face of silicon boules using mid-infrared laser scanning. Issue 26 (15th June 2021) - Jensen, Mathias Novik; Hellesø, Olav Gaute
Abstract : Laser scanning is investigated to measure the deflection of the crystal–melt interface during Czochralski-growth of silicon. Abstract : Laser scanning is investigated to measure the deflection of the crystal–melt interface during Czochralski-growth of silicon. A mid-infrared laser is used to take advantage of the IR-transparency of silicon. The method is tested at room temperature on the end-face of three crystal-samples prematurely separated from the melt ('body-pops'). For these samples, the end-face closely resembles the crystal–melt interface during crystal growth. The laser beam is sent through the crystal boule and detected on the far side, depending on whether it is reflected by the end-face or not. Two scanning methods are tested, one assuming no reflection, i.e. direct transmission, and the second assuming reflection by the end-face, with triangulation used to find the end-face deflection. The transmission scan distinguished the end-face from other changes in transmission in >87% of measurement points along the samples, with the resolution determined by the step-size used (1 mm). The end-face reflection method only worked for two of the three samples, with a mean error of ≤0.3 mm and a standard deviation of ≤0.8 mm. This is sufficient to distinguish normal from abnormal end-face deflections. Challenges for in situ implementation of the methods are discussed.